Comparison of Static and Dynamic Balance of Physically Active College Women with Different Foot Arch Heights - Maryam Panahi; Farideh Babakhani; Foad Seidi (Vesnu Publications, 2016)
Introduction: Balance is one of the pivotal and inseparable components in daily activities and sports performance. Better and more comprehensive recognize of effective factors on quality of balance and how they impress, provide the opportunity which helps to improve motor-base factors in whole life and avoids negative impacts. It seems that anatomical abnormalities such as flat and pescavus foot and morphologic features of the foot can affect motor fitness characteristics like balance. So, this research aimed to compare the static and dynamic balance of women college athletes which have different foot arch heights. Materials and Methods: Static and dynamic balance were assessed in 90 women athletes in three types of foot arch: flat foot (30 persons), pescavus foot (30 persons) and normal foot (30 persons); it was done using stabilometer device with open-eye participant and maintaining a single leg stance (a measure of static balance), while dynamic balance was tested with putting a dominant step on a device (a measure of dynamic balance). Besides, to differentiate between flat, pescavus and normal foot arch, the navicular drop was tested with Brady attributive method. To test and analyze statistical datum, also one-way ANOVA statistical method was used via SPSS19 software. Results: There was a significant difference in total area of the swing movement (P = 0.002) in static balance; however, there is not any significant difference between the study groups in dynamic balance (P = 0.098). Conclusion: Although static balance in person who suffers from flat and pescavus foot arch abnormality is lower than normal foot arch, but in dynamic balance, no significant differences between the three groups of foot arch height were noticed. So, the people who suffers from flat and pescavus foot arch should do their daily activities with more accuracy and attention.